Alceu Amoroso Lima e as posturas políticas na Igreja Católica Brasileira (1930-1950) - Cordeiro, Leandro Luiz (2008)
The main objective of this dissertation is to examine the Catholic intellectual's path Alceu Amoroso Lima (Tristão de Athayde), between 1930 and 1950. Analyzing his thought intended to understand which the factors that took this great protagonist of the brazilian history to migrate of an orthodox and authoritarian catholicism - in short of a position remarkably of right - adopted starting from his conversion to the catholicism in 1928, and that it characterizes his thought during good part of the decade of 1930, to a catholicism more open, progressive - that can be characterized as a political position of left -, in the end of 1940. However, more than answers for this transition, we sought to contemplate the changes and the permanences in his thought, exposing as it was positioned before the most relevant and controversial subjects of this period. Trying to understand better this context we showed which the positioning of the Catholic Church before of the society and of the State, in other words, we evaluated his political positioning in the period. On the other side, looking for to place Alceu Amoroso Lima in the political and catholic debate of the time, we delimited the dispute fields in which it was inserted. Because of this, more than a study the about of the political postures of Alceu Amoroso Lima, the present work was constituted in a study of the political postures in the brazilian Catholic Church.